Islamic leadership today - Fontaine, Rodrigue Ancelot Harvey; Mohd. Israil, Khaliq Ahmad; Gapur, Oziev (ICIFE, 2017)
Characters and competencies matter the most in leadership theories. Conventional institutions have glittering records of training leaders and managers in developing the right competencies but they generally fail in characters building. In 2006, Harry Lewis, the former dean of Harvard College described Harvard as a “university without a soul ”. His analysis of the problems at Harvard was applauded but his proposed solutions seemed vague and unsatisfactory. As Muslims, we sympathise with professor’s Lewis analysis. His observations are important because it indicates that the problems are systemic. They are caused by the system, not by a few bad apples. However, we believe that the solution is simpler. Leaders who believe in God are more likely to act in accordance with God’s injunctions. Muslims believe that such leaders would naturally develop a strong moral character. This moral character will be tested in the rough and tumble of organizational life. Leaders will either make compromises or they will rise to the occasion. In this book, we hope to show that leaders don’t have to compromise on their principles to be successful. Much commendable progress over the last few years was achieved. There has been a huge effort around the world in researching the role of spirituality at work. There is a general agreement that spiritual leaders are more moral and more ethical. We hope to demonstrate that they can still be effective. Within this broad framework, we decided to focus on the universal lessons found in the Qur’an, the scripture of the Muslims as final revelation. To do justice to the Qur’an, we had to first understand the current issues surrounding conventional leadership. This proved much more difficult than we anticipated and it took us nine chapters to discuss the pertinent issues. This constitutes the first part (Part-1) of the book. At the end of these nine chapters, we feel that readers should; 1. Understand the limitations of conventional theories of leadership; and 2. Appreciate that the Qur’an addresses these issues comprehensively. We then try to understand the Prophetic Leadership Model used by the last Prophet (saw) and his Four Successors(r.a.). We try to demonstrate that Islamic leadership is possible today. This has been put in Part-2. This part therefore provides us critical context to understand how the message of the Qur’an should be understood. We cover this in chapters ten, eleven and twelve. Lastly, from chapter thirteen to sixteen, we look at the Qur’anic perspective on the individual responsibilities and on the collective responsibilities of leaders. This is about followership characteristics in general and constitutes the Part-3 of the book. Thus throughout this book, we take a human resource development (HRD) or rightly called Talents Development view on this subject. We believe that there is no point in developing a model if people today cannot be trained to use that model. We therefore report on our experiences in training managers and leaders on how to implement this model, covers the rest part of the book.